Declining Dynamism, Allocative Efficiency, and the Productivity Slowdown - Decker, Ryan A.; Haltiwanger, John; Jarmin, Ron S.; Miranda, Javier (American Economic Review, 2017)
A large literature documents declining measures of business dynamism including high-growth young firm activity and job reallocation. A distinct literature describes a slowdown in the pace of aggregate labor productivity growth. We relate these patterns by studying changes in productivity growth from the late 1990s to the mid 2000s using firm-level data. We find that diminished allocative efficiency gains can account for the productivity slowdown in a manner that interacts with the within-firm productivity growth distribution. The evidence suggests that the decline in dynamism is reason for concern and sheds light on debates about the causes of slowing productivity growth.